(untitled) (Eurasian Journal of Philology Science and Education, 2018)
The state of the genre of the novel and its change in contemporary world literature in one sense or another is also reflected in contemporary Azerbaijani literature. The article talks about the novel in Azerbaijani literature of the period of independence, it reveals the attitude to such concepts as literature and novel. The detective genre that is just separating from the novel is touched upon. The reasons of the readers’ warm approach to this genre as a separate one were put into discussion. The article raises the question of whether the detective is a «serious» literature